Ship or Sheep? An intermidiate pronunciation course - Baker, Ann (Lao động, 2009)
This is a revised and updated edition of the classic pronunciation title Ship or Sheep? This new edition of Ship or Sheep?, an accessible intermediate-level pronunciation course in full colour for students of English, provides systematic practice of English pronunciation, with an emphasis on minimal pairs, through a wide variety of interesting exercises and activities. The course is suitable for classroom use or for self-study